Amorphization induced by 60° shuffle dislocation pileup against different grain boundaries in silicon bicrystal under shear. (15th October 2019) - Chen, Hao; Levitas, Valery I.; Xiong, Liming
Abstract: Molecular dynamics (MD) simulations of the amorphous band nucleation and growth ahead of the tip of a shuffle 60 o dislocation pileup at different grain boundaries (GBs) in diamond-cubic (dc) silicon (Si) bicrystal under shear are performed. Amorphization initiates when the local resolved shear stress reaches approximately the same value required for amorphization in a perfect single crystal (8.6–9.3 GPa) for the same amorphization plane. Since the local stresses at the tip of a dislocation pileup increase when the number of the dislocations in a pileup is increased, the critical applied shear stress τ a p for the formation of an amorphous shear band significantly decreases with the dislocation accumulation at the GBs. In particular, when the number of the dislocations in a pileup increases from 3 to 8, the critical shear stress drops from 4.7 GPa to 1.6 GPa for both the Σ 9 and Σ 19 GBs and from 4.6 GPa to 2.1 GPa for the Σ 3 GB, respectively. After the formation of steps and disordered embryos at the GBs, the atomistic mechanisms responsible for the subsequent amorphous shear band formations near different GBs are found to distinct from each other. For a high-angle GB, such as Σ 3, an amorphous band propagates through the crystalline phase along the ( 112 ) plane. For the Σ 9 GB, dislocations disassociate and the stacking faults form, which then precede the formation of an amorphous band along the ( 110 ) plane. For the Σ 19 GB, the one-layer stacking fault along the ( 111 ) plane transforms into an interesting intermediate phase: a two-layer band with the atomic bonds being aligned along the ( 111 ) plane (i.e., rotated by 30 o with respect to the atomic bonds outside the band). This intermediate phase transforms to the amorphous band along the ( 111 ) plane under a further shearing. The obtained results represent an atomic-level confirmation of the effectiveness of dislocation pileup at the nucleation site for various strain-induced phase transformations (PTs), and exhibit some limitations. Graphical abstract: Image 1